2016
DOI: 10.1002/jor.23440
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast depletion with clodronate liposomes delays fracture healing in mice

Abstract: Osteoclasts are abundant within the fracture callus and also localize at the chondro-osseous junction. However, osteoclast functions during fracture healing are not well defined. Inhibition of osteoclast formation or resorptive activity impairs callus remodeling but does not prevent callus formation. Interestingly, though anti-osteoclast therapies differentially affect resolution of callus cartilage into bone. Treatments that inhibit osteoclast formation or viability tend to impair callus cartilage resolution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
(64 reference statements)
3
27
0
Order By: Relevance
“…injection of clo-lip or a PBS-lip control, and the extent of macrophage depletion was investigated. As clo-lip administration is known to induce apoptosis of all phagocytic cells, including osteoclasts [24], zoledronate was administered to a third group of mice as an osteoclast-depletion control [33]. Flow cytometric analysis revealed a 70% reduction in the total CD11b + F4/80 + monocyte/macrophage population within the BM of clo-lip–treated animals compared with controls (Figure 1 A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…injection of clo-lip or a PBS-lip control, and the extent of macrophage depletion was investigated. As clo-lip administration is known to induce apoptosis of all phagocytic cells, including osteoclasts [24], zoledronate was administered to a third group of mice as an osteoclast-depletion control [33]. Flow cytometric analysis revealed a 70% reduction in the total CD11b + F4/80 + monocyte/macrophage population within the BM of clo-lip–treated animals compared with controls (Figure 1 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulation of clodronate in lipid vesicles specifically targets clodronate to phagocytic macrophages that engulf and degrade the liposome, leading to clodronate accumulation and subsequent cellular apoptosis [23]. Unlike free clodronate, clodronate-liposomes (clo-lip) globally deplete macrophages and other phagocytic cells [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, reports regarding effects of clodronate are conflicting, including no changes in bone mineral density in a callus [ 11 ], 30% increase in bone mineral density [ 10 ], increased calcium content within the callus [ 12 ], and decreased healing callus strength [ 13 ]. Recently, it has been shown that osteoclasts are a necessary component of efficient endochondral ossification during fracture repair in mice [ 14 ]; therefore, it is possible that clodronate may impair normal bone healing in horses, which calls for careful consideration when used in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, liposomal drug delivery can also be detrimental on bone healing as shown by Lin and O'Connor. The authors detected impaired fracture healing of femoral defects after treatment with clodronate-encapsulated liposomes ( Figure 2) over an investigation period of 28 days [166]. Liposomes or micelles are suitable site-directed drug carriers, particularly for water-insoluble drugs due to surface-decorated bone-targeting moieties.…”
Section: Liposomes and Micellesmentioning
confidence: 99%